2005
DOI: 10.1345/aph.1e594
|View full text |Cite
|
Sign up to set email alerts
|

Intentional and Unintentional Nonadherence to Antihypertensive Medication

Abstract: Both intentional and unintentional nonadherence are common and related to perceived adverse effects. Furthermore, different interventions may be necessary to improve adherence in unintentionally and intentionally nonadherent patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
128
1
10

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(150 citation statements)
references
References 25 publications
2
128
1
10
Order By: Relevance
“…18 A secondary analysis using data from the Canadian Heart Health Survey found that hypertensive patients receiving antihypertensive treatment but not achieving the target blood pressure at the 140/90 mm Hg level were more likely to be diabetic and of lower socioeconomic status as compared with those having controlled blood pressure. 19 Previous studies also found that hypertensive patients with low education were more likely to report non-adherence than those with high education, 20 and hospitalization rate was higher for patients with low medication adherence. 21 If less educated individuals are less knowledgeable about the importance of blood pressure control for prevention of diabetic complications, they will be less likely to adherent to therapy than better educated individuals.…”
Section: Discussionmentioning
confidence: 93%
“…18 A secondary analysis using data from the Canadian Heart Health Survey found that hypertensive patients receiving antihypertensive treatment but not achieving the target blood pressure at the 140/90 mm Hg level were more likely to be diabetic and of lower socioeconomic status as compared with those having controlled blood pressure. 19 Previous studies also found that hypertensive patients with low education were more likely to report non-adherence than those with high education, 20 and hospitalization rate was higher for patients with low medication adherence. 21 If less educated individuals are less knowledgeable about the importance of blood pressure control for prevention of diabetic complications, they will be less likely to adherent to therapy than better educated individuals.…”
Section: Discussionmentioning
confidence: 93%
“…The scale for each item was revised to include the response categories strongly agree, agree, disagree, and strongly disagree. Those individuals who reported strongly agree, agree, don't know, or refused to any of the four items were classified as nonadherent (67). Self-report scores as measured by the same scale used in the current study had a sensitivity of 72% and specificity of 74% for ≥80% adherence with antidepressant medication (68).…”
Section: 4mentioning
confidence: 99%
“…Further, our strategy for assessing adherence differed from prior analyses that used pharmacy refill data 10,11 or simply reported current medication use . 5,12 While these measures likely accurately reflect medication prescribing, we used a validated measure that explores patient attitudes toward medicationtaking, 21,22 which in this case may better capture true medication adherence. Though some have questioned the correlation between self-reported and objective medication adherence, 23,24 self-reporting remains among the most common strategies for assessing medication adherence because it is simple and reliable.…”
Section: Younger Agementioning
confidence: 99%